5-Aminolevulinic acid-guided resection improves the overall survival of patients with glioblastoma—a comparative cohort study of 343 patients. Issue 1 (26th March 2021) - Baig Mirza, Asfand; Christodoulides, Ioannis; Lavrador, Jose Pedro; Giamouriadis, Anastasios; Vastani, Amisha; Boardman, Timothy; Ahmed, Razna; Norman, Irena; Murphy, Christopher; Devi, Sharmila; Vergani, Francesco; Gullan, Richard; et al.
Abstract: Background: 5-Aminolevulic acid-guided surgery (5-ALA-GS) improves the extent of resection (EoR) and progression-free survival in patients with glioblastoma multiforme (GBM). Methods: A single-center retrospective cohort study of adult patients with GBM who had surgical resection between 2013 and 2019, 5-ALA guided versus a non-5-ALA cohort. The primary outcome was the overall survival (OS). Secondary outcomes were EoR, performance status (PS), and new focal neurological deficit. Results: Three hundred and forty-three patients were included: 253 patients in 5-ALA-GS group and 90 patients in the non-5-ALA-GS group. The OS (17.47 vs 10.63 months, P < .0001), postoperative PS ( P < .0001), PS at 6 months ( P = .002), new focal neurological deficit (23.3% vs 44.9%, P < .0001), and radiological EoR (gross total resection [GTR]—47.4% vs 22.9%, P < .0001) were significantly better in the 5-ALA-GS group compared to non-5-ALA-GS group. In multivariate analysis, use of 5-ALA ( P = .003) and MGMT promoter methylation ( P = .001) were significantly related with a better OS. In patients with radiological GTR, OS was also significantly better ( P < .0001) in the 5-ALA-GS group compared to the non-5-ALA-GS group. Conclusions: 5-ALA-GS is associated with a significant improvement in the OS, PS after surgery and at 6 months, larger EoR, and fewer new motor deficits in patients with GBM.